Assessment of Exposure to Toluene and Xylene and its Impact on the Work Capacity of Fishermen: A Case Study in Rayong Province, Thailand - Lormphongs, Srirat (Disease and Health Research: New Insights Vol. 8, 2024)
Background: The fishermen, who often depart at dawn and return in the late evening, are consistently exposed to these hazardous chemicals with little to no use of protective equipment or apparatus, which raises significant concerns regarding their occupational safety and respiratory health. Aims: To better understand the occupational hazards faced by fishermen, this study aims to investigate the daily exposure to toluene and xylene from the petrol used in the combustible engines of small fishing boats. The study seeks to quantify the levels of exposure, assess the associated health risks, and explore potential measures to improve occupational safety standards among this vulnerable group. Study Design: It was a cross-sectional study. Place and Duration of Study: The study was conducted in the Amphur Muang District of Rayong Province, Thailand. Methodology: The study group was a group of small boat fishermen totaling 120 persons. The materials used in this study were a questionnaire comprised of various sections used to collect occupational data, the collection of air samples, and urine samples. Results: The study involved 120 fishermen with a mean age of 44.98 years. Of these, 81.6% worked 7 hours or less per day, and 68.0% worked all 7 days of the week. Only 0.8% consistently used respiratory protection, and among those who did, the only type of mask used was cotton. After a day's work, over 30% of the fishermen reported symptoms of adverse health effects, such as headaches, general fatigue, fatigue in the arms and legs, and coughing. Despite these symptoms, most participants (69.2%) demonstrated good work capacity. Air samples were collected using individual "Organic Vapor Monitors (3M 3500)" attached to the lapels of each participant. The average Toluene level was 29.61 ± 53.93 ppb, and the average Xylene level was 248.86 ± 41.64 ppb. Urine samples collected after the work shift showed an average hippuric acid level of 391.47 ± 391.31 mg/g creatinine and an average methyl hippuric acid level of 73.04 ± 178.05 mg/g creatinine. No significant relationship was found between the levels of toluene, xylene, hippuric acid, methyl hippuric acid, and the work capacity of the fishermen. Conclusion: Fishermen working on small fishing boats are at significant risk of exposure to toluene and xylene in their work environment. Therefore, they must be educated and made aware of the dangers these chemicals pose in their daily activities. It is crucial to use appropriate personal protective equipment when operating fishing boats with petrol engines.